Texting and Driving: Can it be Explained by the General Theory of Crime? - Quisenberry, Phillip Neil (American journal of criminal justice, 2015)
There has been quite a bit of media attention devoted recently to the topic of distracted driving generally, and texting and driving specifically. Recent studies by scholars, as well as the Department of Transportation, have continued to demonstrate the dangers of texting while driving. Previous studies have found that texting while driving reduces reaction and control times even more than drinking and driving. At least one study found that drivers who text are 23 times more likely to crash relative to non-distracted drivers. Tougher laws may be alluring as a deterrent to this behavior, but according to the data in this study, 96 % of respondents knew it was against the law but continued to text and drive anyway. This finding casts doubt on the effectiveness of any new distracted driving laws. The general theory of crime (Gottfredson & Hirschi, 1990 ) posits that levels of self-control are tied to deviant behaviors such as texting while driving. Other studies have also found that levels of self-control were significantly tied to other dangerous driving behaviors such as driving while drinking and driving without using a seatbelt. The findings in this study add support to the general theory of crime by demonstrating that, among college students in this sample, higher self-control significantly reduces the amount of texting while driving.